2013
DOI: 10.1136/postgradmedj-2012-131393
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in UK patients with hospital-acquired bacteraemia and the risk of catheter-associated urinary tract infections

Abstract: PurposeThere is lack of contemporary outcome data on patients with hospital-acquired infections that cause bacteraemia. We determined the risk factors for 7-day mortality and investigated the hypothesis that, compared with central venous catheter (CVC)-associated bacteraemic infections, catheter-associated bacteraemic urinary tract infections (UTIs) were significantly associated with 7-day mortality.MethodsFrom October 2007 to September 2008, demographical, clinical and microbiological data were collected on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 24 publications
2
41
1
2
Order By: Relevance
“…The Pitt bacteremia score is a marker of severity of illness in patients with nBSIs and patients with scores >4 are considered to be critically ill. In line with the results of previous studies (Neuner et al, 2011;Retamar et al, 2011;Melzer and Welch, 2013), in our hospital the Pitt bacteremia score was strongly correlated with 28-d mortality. Compared with CLABSI, we demonstrated a significant association between urinary tract source of BSI and death at 28 d. This result has also been validated in a multi-center study in the UK (Melzer and Welch, 2013).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The Pitt bacteremia score is a marker of severity of illness in patients with nBSIs and patients with scores >4 are considered to be critically ill. In line with the results of previous studies (Neuner et al, 2011;Retamar et al, 2011;Melzer and Welch, 2013), in our hospital the Pitt bacteremia score was strongly correlated with 28-d mortality. Compared with CLABSI, we demonstrated a significant association between urinary tract source of BSI and death at 28 d. This result has also been validated in a multi-center study in the UK (Melzer and Welch, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…In line with the results of previous studies (Neuner et al, 2011;Retamar et al, 2011;Melzer and Welch, 2013), in our hospital the Pitt bacteremia score was strongly correlated with 28-d mortality. Compared with CLABSI, we demonstrated a significant association between urinary tract source of BSI and death at 28 d. This result has also been validated in a multi-center study in the UK (Melzer and Welch, 2013). However, appropriate empirical therapy can protect patients from mortality at 28 d. The mortality rate was reduced by approximately 4-fold in patients receiving appropriate empirical therapy compared to those without (OR=0.23, P=0.001).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Catheterassociated urinary tract infections (CAUTIs) have not been as extensively studied in pediatric populations, but are associated with poor outcomes among adults. 5,6 Health care-associated infections (HAIs) result in protracted hospital stays, 1 increased cost, [7][8][9] and prolonged need for mechanical ventilation. 3 They are also associated with poor neurodevelopmental outcomes, particularly for extremely low birth weight infants.…”
mentioning
confidence: 99%
“…23 Moreover, it has been observed that infections related to bladder catheters are associated with a higher mortality at 7 days compared with patients with central venous vascular catheter, regardless of comorbidity and age of patients. 24 Interestingly, sepsis seems to exhibit different outcome depending on gender. On one hand, women are infected more frequently than men, and the risk of bacteremia increases after the age of 60 years.…”
Section: Discussionmentioning
confidence: 99%